THE ROLE OF DIVERSIFICATION OF BANKING SERVICES IN THE PROFITABILITY OF COMMERCIAL BANKS: (AN ANALYTICAL STUDY IN THE SUMER COMMERCIAL BANK AND THE INTERNATIONAL DEVELOPMENT BANK) - A.P.Dr. Rahim Shrad Amer Al-Taie; Ibrahim Qais Ibrahim Al-Qaisi (Scholar Express Journals, 2023)
This study was prepared to demonstrate the role of diversification of banking services in the profitability of private Iraqi commercial banks. international development), and the research tended to follow the inductive approach, the descriptive approach, and the analytical approach by studying the theoretical framework for diversifying banking services, indicators of profitability in commercial banks, the most important ratios measured, and analyzing the effects left by the diversification of banking services on the profitability of Iraqi private commercial banks, the research sample, in order to strive to achieve the goals set by him and trying to reach them by conducting this type of research.
Keywords: diversification of banking services; the profitability of commercial banks